Efektivitas Konseling Kelompok Pada Ibu-Ibu Yang Mengalami Anxietas Pasca Konflik Di Kecamatan Nisam, Aceh Utara - Rahmia Dewi (Jurnal Psikologi Terapan, 2020)
This study aims to examine more deeply the effectiveness of group counseling in mothers who experience post-conflict anxiety in the district of Nisam, North Aceh. This research approach uses qualitative research with explorative type of research through psychological counseling group analysis. The selection of the subjects of this study uses 4 purposive sampling techniques, namely Nisam residents who experienced the effects of conflict in North Aceh, Aceh-Indonesia Province. Data collection methods used in this study using direct observation methods involved passively, in-depth interviews and documentation in the form of group counseling, instruments used using the Hopkins Symptom Checklist-25 (HSCL-25) to measure the level of anxiety in research subjects and prepare forms to measure the effectiveness of group counseling based on psychological aspects as well as the interview form. Data analysis techniques used from Creswell by means of theme analysis and then interpreting the findings in the field. The results showed that the research conducted on mothers of conflict victims, they still experience anxiety until now, after a group counseling session, the anxiety they felt anxiety decreased. Counseling activities that have been carried out have a positive impact on the physical and psychological development.